The Tempest - "Shakespeare" (Sweet cherry publishing: China, 2013)
The Tempest is a comedy that was written by William Shakespeare. The action centers around a sorcerer named Prospero, who is the rightful Duke of Milan, as he plans to restore his daughter's place in society through manipulation. Though The Tempest was listed as a comedy in Shakespeare's First Folio it is now often considered to be a tragicomedy
Keywords: Adaptations Juvenile literature